Conservative management of an extensive odontogenic keratocyst in the anterior region of a pediatric patient’s jaw (Research, Society and Development, 2021)
Odontogenic keratocysts (OKCs) are now considered benign cysts of odontogenic origin that are characterized by an aggressive behavior with a relatively high recurrence rate, particularly when OKCs are associated with syndromes. Its histological appearance is characteristic with the presence of an epithelial lining parakeratinized showing a corrugated surface, together with a number of architectural features of the epithelium as a thickness of six to eight layers and the presence of columns, palisade basal cell. Radiographically, the lesion is often unilocular radiolucent surrounded by margins smooth or jagged edges with sclerotic. OKCs are more frequently in the third decade of life. This article reports a case of a young patient with exuberant OKC on unusual anterior mandibular site underwent treatment that involved a 48-month period of decompression, followed by enucleation of the residual cyst. Preserving important structures of the bone and soft tissue decompression is a method with low morbidity. In addition, according to the literature, decompression has a success rate at least as high as the one of most aggressive treatments.